PENGEMBANGAN OBYEK WISATA MATANTIMALI DALAM UPAYA MENINGKATKAN KUNJUNGAN WISATA KOTA PALU - Deni Dwi Ananti; Andi Pebrianto (Kepariwisataan: Jurnal Ilmiah, 2020)
This study aims to determine the management of Matantimali tourism objects and constraints faced in the management of Matantimali. the writing of this Scientific Article is presented in a descriptive qualitative manner to provide an overview and information about Matantimali tourism objects. Methods of collecting data using observation, interviews, documents, and questionnaires. the data obtained were then analyzed qualitatively and presented descriptively. The results of the study indicate that Matantimali tourism objects have potential but the lack of funds is one of the obstacles so that this potential has not been widely developed. The management of Matantimali tourism objects is currently still managed by the local community because of the absence of regulations with the local government. With sufficient human resources plus the right education and management Matantimali will be beneficial for improving the economy of the surrounding community.Keywords: Tourism Development, Tourism Management, Tourism Attraction